Mangrove gastropod distribution based on dominant vegetation classes and their relationship with physicochemical characteristics on fringe mangroves of Lembongan Island, Bali, Indonesia - NI MADE ERNAWATI; AYU PUTU WIWEKA KRISNA DEWI; I PUTU SUGIANA; I WAYAN EKA DHARMAWAN; MIFTACHUDIN SYAIFUL MA'RUF; GEMMA ANTONIA GALGANI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ernawati NM, Dewi APWK, Sugiana IP, Dharmawan IWE, Ma’ruf MS, Galgani GA. 2024. Mangrove gastropod distribution based on dominant vegetation classes and their relationship with physicochemical characteristics on fringe mangroves of Lembongan Island, Bali, Indonesia. Biodiversitas 25: 156-166. Mangrove ecosystems are important in supporting diverse marine life, offering refuge, reproductive grounds, and sustenance to various species. However, mangroves possess distinct zoning patterns determined by dominant species due to environmental variations that significantly impact the biodiversity of biota, particularly gastropods. A study on the Indonesian island of Nusa Lembongan revealed distinct communities of coexisting gastropod species in each mangrove vegetation zone. We discovered 29 distinct species of mangrove gastropods, with the Sonneratia mangrove zone having the most and the Lumnitzera zone having the least. Certain species, including Amphidromus perversus, Cerithium adustum, and Echinolittorina sundaica, were detected in only one of the mangrove zones. In each mangrove zone, the composition of gastropod species changed depending on the substrate type, e.g., soil, mangrove trunks, or mangrove leaves. The Shannon-Wiener diversity index values range from low to high diversity, and the community structure index values in mangrove zones vary. The evenness index varied by region, with Avicennia, Bruguiera, and Sonneratia having the highest index value. The findings indicate that mangrove vegetation zones are essential for maintaining diverse gastropod populations, with distinct composition and abundance patterns influenced by the distance of each mangrove zone from the ocean. This data may influence conservation efforts to preserve mangrove habitats and the diverse array of organisms that depend on them.